PROFESSIONAL COMPETENCE OF A MODERN TEACHER SERVICE WORK (Pedagogy of Higher and Secondary Education, 2008)
In the article the question of study of problem of professional competence of modern huu her of labour studies is examined on the basis of personality - the oriented technology of. For of the best preparation of specialist an author offers application of project technology which will allow to untie the put tasks.